2023
DOI: 10.3390/su15129756
|View full text |Cite
|
Sign up to set email alerts
|

Fires in Waste Treatment Facilities: Challenges and Solutions from a Fire Investigation Perspective

Wen-Yen Juan,
Chia-Lung Wu,
Fan-Wei Liu
et al.

Abstract: Fires in waste treatment facilities have significant social, economic, and environmental implications. Factors such as self-heating of lithium-ion batteries, thermal runaway, friction, human activities, technical errors, and unfavorable storage conditions contribute to these fires. High-risk categories include illegal dumping sites, recycle collection stations, and wood-related facilities. The frequency of fires in waste treatment facilities and the emergence of new waste types have led to public discontent. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most of them possibly appeared because of fires sometimes occurring in MWLs [ 44 ] as the result of a combustion process. According to study [ 45 ], substances such as pyrene, anthracene, and fluoranthene, which form during combustion, were detected in soil and air samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them possibly appeared because of fires sometimes occurring in MWLs [ 44 ] as the result of a combustion process. According to study [ 45 ], substances such as pyrene, anthracene, and fluoranthene, which form during combustion, were detected in soil and air samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the composition of the deposited waste, various toxic compounds can be emitted during a fire [7,10,11]. Storage site fires can pose a substantial environmental threat through air, groundwater, surface water, soil, and crop pollution [12][13][14]. A survey conducted by Raudonyt ė-Svirbutavičien ė et al has shown the presence of high quantities of heavy metals (HMs), trace elements, mutagenic compounds, toxic and carcinogenic substances, such as volatile organic compounds (VOCs) and polycyclic aromatic hydrocarbons (PAHs), as well as solid particles [15].…”
Section: Introductionmentioning
confidence: 99%